1995
DOI: 10.1093/carcin/16.9.2045
|View full text |Cite
|
Sign up to set email alerts
|

Formation of 8-nitroguanine by the reaction of guanine with peroxynitrite in vitro

Abstract: Nitric oxide and superoxide anion, both formed in inflamed tissues, react rapidly to form the peroxynitrite anion (ONOO-), a strong oxidant which can initiate reactions characteristic of hydroxyl radical (HO.), nitronium ion (NO2+) and nitrogen dioxide radical (NO2.). Peroxynitrite, therefore, may cause DNA or tissue damage, contributing to the multistage carcinogenesis process. We have studied reactions of various bases, nucleosides or deoxynucleosides with peroxynitrite in vitro. Guanine reacted rapidly with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
205
0
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 305 publications
(214 citation statements)
references
References 0 publications
8
205
0
1
Order By: Relevance
“…The acid-hydrolyzed DNA was purified by preparative HPLC and the fractions containing nitroSGua were collected and evaporated to dryness. This concentrated fraction was analyzed by HPLC with UV detection at 396 nm, as previously reported [20]. A yellow peak eluted at the same retention time as a standard nitro8Gua (7.8 min).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The acid-hydrolyzed DNA was purified by preparative HPLC and the fractions containing nitroSGua were collected and evaporated to dryness. This concentrated fraction was analyzed by HPLC with UV detection at 396 nm, as previously reported [20]. A yellow peak eluted at the same retention time as a standard nitro8Gua (7.8 min).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that peroxynitrite induces strand breaks in plasmid DNA [18] and oxidative damage in isolated DNA in vitro [19]. We recently found that guanine reacts rapidly with peroxynitrite under physiological conditions to form several substances, two of which are yellow [20]. On the basis of chromatographic and spectral evidence we identified the major compound (which accounts for about 80% of all compounds formed) as a novel adduct, 8-nitroguanine (nitroSGua) [20].…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Under these conditions, NO will react rapidly with superoxide anion to form ONOO. The relativities of the free radical NO and superoxide anion were found to be relatively low, but their metabolite ONOO -was extremely reactive and directly induced toxic reactions, including SH-group oxidation, protein tyrosine nitration, lipid peroxidation and DNA modifications (Yermilov et al 1995;Babu et al 2001). Coriandrum sativum showed antioxidant activity, with IC 50 values of 815.6 μg/ml and standard BHA with 49.1 μg/ml.…”
Section: Dpph Scavenging Abilitymentioning
confidence: 97%